Correction: Wang et al. Antibacterial Efficacy of Feline-Derived Lactic Acid Bacteria against Enteropathogenic Escherichia coli: A Comprehensive In Vitro Analysis. Fermentation 2024, 10, 514 - Weiwei Wang; Hao Dong; Qianqian Chen; Xiaohan Chang; Longjiao Wang; Chengyi Miao; Shuxing Chen; Lishui Chen; Ran Wang; Shaoyang Ge; Wei Xiong (Fermentation)
Some paragraphs were missing from the original publication [...]